Formal Classification of Medical Concept Descriptions: Graph-Oriented Operators - Bernauer, J.; Schoop, D. (Methods of Information in Medicine, 1998)
A crucial component of a medical concept representation system is the classifier. It requires features that are not sufficiently supported by current logic based formalisms like description logics and conceptual graphs. Those features are, for instance, the representation of partitive and spatial relations and their impact on sUbsumption. This paper introduces graph oriented classification operators for a concept representation language with normal forms. Emphasis is on the separation of generic and partitive relations and on the mutual interdependence of sUbsumption and part-whole. For that purpose operators are given for formal subsumption, formal part-whole, subsumptive part-whole and part-sensitive subsumption. These operators are based on the formal structure of concept descriptions and on explicitly introduced generic and partitive relationships between their constituents.
Keywords: Conceptual Graphs; Medical Concept Representation; Terminology Models; Formal Classification; Part-whole Relation